Effects of travel distance and season of the year on transport-related mortality in cattle - Simova, Veronika; Voslarova, Eva; Vecerek, Vladimir; Passantino, Annamaria; Bedanova, Iveta (Animal science journal, 2017)
The number of animals that die during transport to a slaughterhouse or shortly after being delivered to a slaughterhouse may serve as an indicator of animal welfare during transport. The aim of this study was to determine the mortality rate in cattle resulting from transport to slaughter in the Czech Republic in the period from 2009 to 2014, and to investigate the effect of travel distance and season of the year. Transport-related mortality rates were recorded for all categories of cattle for the following travel distances: up to 50 km, 51-100 km, 101-200 km and over 200 km. Higher mortality rates occurred with shorter travel distances (<50 km and 51-100 km) when compared to longer travel distances (101-200 km and > 200 km), with a significant difference (P < 0.01) between short and long travel distances being found in feeders and dairy cows. Also, the season of the year had a significant impact on the mortality rate among transported cattle. The highest mortality rate in all categories was observed in spring months. The lowest mortality rate was found in autumn months for fat cattle and dairy cows and in winter months for feeders and calves.
Keywords: mortalita; Temperature; Transportation; doprava; teplota; Female; pohoda zvířat; Abattoirs; zvířata; Mortality; časové faktory; roční období; Cattle; ženské pohlaví; Male; Seasons; jatka; Czech Republic; skot; Animals; Česká republika; mužské pohlaví; Animal Welfare; Time Factors